Las inteligencias múltiples y su influencia en el aprendizaje de los estudiantes de sexto grado paralelo “A” en la asignatura de Lengua y Literatura de la Escuela de Educación Básica Dr. Luis Felipe Zapater Álvarez Blanco, periodo académico 2021-2022. - Salinas Sanchez, Valeria Vermariz (2022)
The current searching work named: The multiple intelligences and their influence in the learning of the students of sixth grade, parallel A, in the subject of Language and Literature of the Dr. Luis Felipe Zapater, basic education school, academic period 2021- 2022 has as a general objective to determine the effects of the multiple intelligences in the learning of the students of sixth grade of the Dr. Luis Felipe Zapater basic education school, academic period 2021- 2022; getting a great learning improvement. During the process of this investigation, it works with different methods which help us to clarify and sustain the different authors premises as well as inferring in criteria to deep in the determined topics. The population was formed by twenty-four students, and two basic education teachers who helped us to demystify the problematic through a question bank related to the investigation work. Moreover, the applied methodology was of descriptive and explorative category, with a mixture study type; for this, we applied methods such as: descriptive, analytic, syntactic, inductive, deductive, and statistic; methods that allow to carry out this investigation process. The gotten results guarantee us to draw conclusion that the multiple intelligences have a great influence in the students’ learning, so that, the multiple intelligences as learning strategies focus on assisting to all students at the same way through the application of activities that encourage and promote the multiple intelligences equally in the learning process, developing unique capacities in the students. Key words: Multiple intelligences, learning strategies, learning techniques.